Conflicto armado y justicia transicional en Colombia: Continuidades y discontinuidades en el proceso de construcción de paz - Lázaro, Julián Andrés (Corporación Universitaria Americana, 2022)
This text is the result of the joint work of an interdisciplinary group of research professors of the Corporación Universitaria Americana who have been working on issues of conflict and peace from its different facets and actors. The question this book seeks to answer is: what are the determining factors in the continuities and discontinuities that the peacebuilding process in Colombia has experienced? In order to answer this question, a historical, political and legal approach to the Colombian armed conflict is combined.